Advances in energy harvesting methods - Elvin, Niell; Erturk, Alper (Springer, 2013)
Advances in Energy Harvesting Methods presents a state-of-the-art understanding of diverse aspects of energy harvesting with a focus on: broadband energy conversion, new concepts in electronic circuits, and novel materials. This book covers recent advances in energy harvesting using different transduction mechanisms; these include methods of performance enhancement using nonlinear effects, non-harmonic forms of excitation and non-resonant energy harvesting, fluidic energy harvesting, and advances in both low-power electronics as well as material science.- Resumé vydavatel
Keywords: alternativní energetické zdroje; přeměna energie; alternative energy sources; energy conversion; elektronické knihy; sborníky; electronic books; papers of several authors